(untitled) (MAUSAM, 1978)
A one dimensional boundary layer model has been used to investigate the influence of solar radiation and the large diurnal variation of surface temperature on the low-level turbulence in the atmosphere over NW India. The model is based on Eulerian conservation equations for momentum, heat, moisture and pollutants and is capable of examining the transport and diffusion processes in the atmospheric boundary layer. The simulation experiment has been conducted for a period of 48 hours based on initial set of meteorological observations collected during 24-26 April 1966 at New Delhi in NW India and the model results of vertical structure of the atmospheric boundary layer and the turbulent heat fluxes at the interface are discussed in this paper.